Improving English Learning Outcomes Through a Quantum Teaching Model - Laily Nurmalia (English Language in Focus (ELIF), 2020)
This research was motivated by the low level of primary English learning outcomes at SDN 02 Cireundeu. It can be seen that there were 21 out of 25 primary learners had a below minimum of completeness criteria (KKM). The objective of the research is indeed to increase the outcomes of primary English learners through a quantum teaching model. Classroom Action Research (CAR), a reflective and collaborative research focused on raising the teaching process quality, was preferred as a research method. The current study used the Kemmis and McTaggart principles, which cover four phases: planning, action, observation, and reflection. The 25 fifth-grade primary English learners, 11 males, and 14 females have participated in this study. Two-cycle actions have been carried out to achieve success criteria of completeness. Based on the results, the quantum teaching model implementation has led to an improvement in the results of each cycle. It can be shown that the students' outcome in Cycle I was 36%, while in Cycle II was 64%. These findings revealed that improvement has been achieved in Cycle II and the completeness criteria have been accepted. In a conclusion, English learning outcomes were significantly improved by implementing a quantum teaching model to the fifth grade of primary learners at SDN 02 Cireundeu.